Pre-arrest and intra-arrest prognostic factors associated with survival following traumatic out-of-hospital cardiac arrest – A systematic review and meta-analysis. (August 2020) - Tran, Alexandre; Fernando, Shannon M.; Rochwerg, Bram; Vaillancourt, Christian; Inaba, Kenji; Kyeremanteng, Kwadwo; Nolan, Jerry P.; McCredie, Victoria A.; Petrosoniak, Andrew; Hicks, Christopher; Haut, Elliott R.; Perry, Jeffrey J.
Abstract: Aim: To summarize the prognostic associations of pre- and intra-arrest factors with return of spontaneous circulation (ROSC) and survival (in-hospital or 30 days) after traumatic out-of-hospital cardiac arrest. Methods: We conducted this review in accordance with the PRISMA and CHARMS guidelines. We searched Medline, Pubmed, Embase, Scopus, Web of Science and the Cochrane Database of Systematic Reviews from inception through December 1st, 2019. We included English language studies evaluating pre- and intra-arrest prognostic factors following penetrating or blunt traumatic OHCA. Risk of bias was assessed using the QUIPS tool. We pooled unadjusted odds ratios using random-effects models and presented adjusted odds ratios with 95% confidence intervals. We used the GRADE method to describe certainty. Results: We included 53 studies involving 37, 528 patients. The most important predictors of survival were presence of cardiac motion on ultrasound (odds ratio 33.91, 1.87–613.42, low certainty) or a shockable initial cardiac rhythm (odds ratio 7.29, 5.09–10.44, moderate certainty), based on pooled unadjusted analyses. Importantly, mechanism of injury was not associated with either ROSC (odds ratio 0.97, 0.51–1.85, very low certainty) or survival (odds ratio 1.40, 0.79–2.48, very low certainty). Conclusion: This review provides very low to moderate certainty evidence that pre- and intra-arrest prognostic factors following penetrating or blunt traumatic OHCA predict ROSC and survival. This evidence is primarily based on unadjusted data. Further well-designed studies with larger cohorts are warranted to test the adjusted prognostic ability of pre- and intra-arrest factors and guide therapeutic decision-making.